Multimedia Signal Coding and Transmission - Ohm, Jens-Rainer.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This textbook covers the theoretical background of one- and multidimensional signal processing, statistical analysis and modelling, coding and information theory with regard to the principles and design of image, video and audio compression systems. The theoretical concepts are augmented by practical examples of algorithms for multimedia signal coding technology, and related transmission aspects. On this basis, principles behind multimedia coding standards, including most recent developments like High Efficiency Video Coding, can be well understood. Furthermore, potential advances in future development are pointed out. Numerous figures and examples help to illustrate the concepts covered. The book was developed on the basis of a graduate-level university course, and most chapters are supplemented by exercises. The book is also a self-contained introduction both for researchers and developers of multimedia compression systems in industry.
Introduction -- Fundamentals -- Perception and Quality -- Quantization and Coding -- Methods of Signal Compression -- Intra-picture Coding -- Inter-picture Coding -- Speech and Audio Coding -- Transmission and Storage of Multimedia Data.
Keywords: Engineering; Coding theory; Electrical engineering; Engineering; Communications Engineering, Networks; Coding and Information Theory; Signal, Image and Speech Processing; Electronic books